Phylogenetic and expression analyses of HSF gene families in wheat (Triticum aestivum L.) and characterization of TaHSFB4-2B under abiotic stress - Yun, Liu; Zhang, Yan; Li, Shi; Yang, Jingyu; Wang, Changyu; Zheng, Lanjie; Ji, Li; Yang, Jiaheng; Song, Linhu; Shi, Yong; Zheng, Xu; Zhang, Zhiyong; et al. (Frontiers in Plant Science, 2023)
Heat shock transcription factors (HSFs) exist widely in plants, recent studies indicated that HSFs, including HSFBs, are multifunctional genes engaged in plant development and growth, as well as in response to abiotic stresses. There are 78 identified TaHSF genes in wheat, we analyzed phylogenetic relationship with amnio acid of TaHSF proteins and collinearity of TaHSF genes in this study. The abiotic stress cis-elements on promoters, tissue specific expression and response to abiotic stresses in TaHSF and AtHSFs were also analyzed. In view that the function of HSFBs in abiotic stresses and the underling mechanism need to be revealed. Here we cloned the homologous gene of AtHSFB4 from wheat variety Chinese spring, designated TaHSFB4-2B based on the gene family classification and chromosomal location on wheat genome. Protein domain prediction indicated TaHSFB4-2B contained an HSF-DNA binding domain. Tissue specific expression analysis showed that TaHSFB4-2B was high transcription level in roots and stems. Subcellular localization analysis showed that TaHSFB4-2B was localized in the nucleus. Heat shock, cold, high salt and drought stress up-regulated transcription level of TaHSFB4-2B in young leaves and young roots of wheat, except in leaves under mocked drought stress, which showed a decreased transcription of TaHSFB4-2B. Overexpression of TaHSFB4-2B suppressed seed germination and growth of Arabidopsis under high salt and drought treatment and affected expression of stress corresponding genes, including AtHSP17.8, AtHSP17.6A, AtHSP17.6C, CAT2, SOS1, under both normal, high salt and drought conditions. We propose TaHSFB4-2B functions as a negative factor to abiotic stress tolerance in plant.